(untitled) - Folsom, Ralph H. (Minnesota, 1996)
This book covers the commencement, insuring, operation and withdrawal of foreign investment, including business immigration, expropriation, goverment imposed restrictions on imports and exports, the GATT/WTO, and economic integration with an emphasis on the European Union and the North American Free Trade Agreement.
Keywords: Commercial law,Export sales contracts,Foreign trade regulation,International business enterprises; Law and gegislation